Comparison between Public and Private Pay Structures in Bangladesh (Journal of Science Foundation, 2013)
A survey was carried out during the period from July to December 2002 to see comparison between public and private pay structures in Bangladesh. To evaluate the public pay structure 120 respondents of Bangladesh Agricultural University (BAU) were interviewed through semi-structured questionnaire. The respondents were categorized in 8 different categories. Information of their monthly salary, income tax etc. were checked against their pay-bills and income tax information as supplier by the employer. The secondary data on also collected personally by researcher himselves Pay-structure of different organizations, National pay scales and Price indices. It was found that almost all employees including teachers and officers are facing constraints to maintain their families with income from their job. About 65.5% of their expenditure is getting from their salaries. More than 36% of the employees (including teachers and officers) failed to manage their family expenditure with income from job and extra job. National Pay scale 1997 reduced sufficiently the disparity between the highest and the lowest salary to 10:1 whereas in 1991 the ratio was 11.11:1. In private sectors like Pubali Bank Limited (PBL), Islami Bank Bangladesh Limited (IBL) and Uttara Bank Limited (UBL) the disparity between the highest and the lowest salary were found 21.1:1, 25.29:1 and 26:1 respectively. But disparity in NPS does not ensure the equity, fairness and justice to the civil servants or employees because salaries were not sufficient to cover the cost of as well as livelihood. The maximum salary one can draw is TK.23800 when a person is in the highest grade according to NPS 1997. On the other hand, in private organizations one can draw the highest amount of TK. 90500 which is more than 3.80 times of the highest amount drawn as per NPS 1997. House rent of private sectors varies from 65.4% to 104% (including house maintenance) where as in public sectors it varies from 40% to 55% of basic salary. Consequently, the living conditions of the service holders of lower income groups have been drastically reducing. The minimum salary ratio is to be suggested between the highest and the lowest position should be 5:1. DOI: http://dx.doi.org/10.3329/jsf.v8i1-2.14631 J. Sci. Foundation, 8(1&2): 89-96, June-December 2010